Foreign Direct Investment in Nepal: A Comprehensive Analysis of Trends, Challenges, and Strategic Pathways - Lamichhane, Durga; Pandey, Chandra Lal (NPRC Journal of Multidisciplinary Research, 2026)
Background: Nepal relies Foreign Direct Investment (FDI) for economic transformation, however, faces a critical challenge in converting approved commitments into actual inflows. Despite progressive policy reforms including the One Stop Service Centre and Automatic Route approval, systematic implementation barriers persist.Methods: This study employs qualitative research examining the secondary data analysis of FDI trends from 2069/69 to 2080/92. Data sources include the Department of Industry Annual, Investment Board Nepal, Nepal Rastra Bank and other empirical researches. Analytical techniques include commitment inflow ratio analysis, sectoral decomposition and comparative regional assessment.Result: Analysis reveals only 38.9% of approved FDI commitments materialize as actual inflows, representing a 61% realization gap; sectoral composition shifted dramatically from energy dominance (80% in 2071/72) to service and tourism (83% in 2080/81). Geographic concentration remains high with China and India accounting for 66.88% of cumulative and human capital constraints constitutes primary implementations barriers.Conclusion: Although Nepal’s FDI environment faces low investment realization rates, infrastructure deficits and institutional limitations, considerable opportunities remain. Closing the commitment realization gap requires better infrastructure, streamlined approvals, targeted incentives and greater geographic diversification. With sustained implementation, Nepal holds strong potential to attract foreign investment and become a regionally competitive destination.Novelty: This research provides a comprehensive empirical assessment of Nepal's FDI landscape through 2081/82, quantifying the commitment realization gap and offering evidence- based policy interventions grounded in current data rather than historical analysis.